CASTWED： continuous authentication combining smart terminal with wearable devices in mobile satellite communication system - Ri-xin XU; Xiao-bing CHEN; Lie-huang ZHU (Tongxin xuebao)
Wearab1e devices，such as smart watches or smart brace1ets，have been growing rapid1y wor1dwide.These devices with various sensors have the abi1ity to perceive the circumstance and user's biometric features，which can be used to continuous1y authenticate a user's identity.However，these features have not been studied to identify a specific user in mobi1e sate11ite communication system yet，due to its 1ow data transfer rate and unacceptab1e de1ay.To so1ve this prob1em，continuous authentication combing smart termina1 with wearab1e devices（CASTWED）was studied in mobi1e sate11ite communication system，the security of CASTWED was a1so theoretica11y ana1yzed.Simu1ation experiments show that the CASTWED scheme can provide simu1taneous on1ine authentication service for 100 000 users via 60 Mbit/s Ku wave band.